NEUROLEADERSHIP IN HOSPITAL SETTINGS: A SYSTEMATIC REVIEW OF MECHANISMS, APPLICATIONS, AND EVIDENCE GAPS - Tazuyyun, Shanaz Hanani; Savira, Tsalsa Dzikria; Kurnia, Jodii Arlan; Yueniwati, Yuyun; Widyaningrum, Kurnia (MNJ (Malang Neurology Journal), 2026)
Background: Background: Systems in healthcare have become more complicated. Advanced leadership skills need to include the cognitive, emotional, and social aspects. An emerging cross-disciplinary field, neuroleadership, combines neuroscience and leadership, but its use in hospitals is still sparse and further underexplored. Objective: The purpose of this paper is to provide a systematic overview to identify the mechanisms, applications, and research gaps of neuroleadership in hospitals. Methods: A systematic review of the literature was conducted following the PRISMA 2020 guidelines. Searches were conducted in PubMed, Scopus, ProQuest, EBSCO, and ScienceDirect by using a set of predetermined keywords. Studies that were eligible and published in the last 10 years were screened, and the methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tool. Results: Nine studies were included in the final review. Findings showed that neuroleadership improves leadership effectiveness via emotional control, cognitive mobility, and social impact. The SCARF (Status, Certainty, Autonomy, Relatedness, Fairness) model was the most used framework in addressing interpersonal relations, engagement of employees, and change in the organization. Neuroleadership is also viewed to enhance transformational leadership by the neurocognitive rationale of motivation and judgment. However, there is a preponderance of conceptual studies over empirical studies. Conclusion: Neuroleadership is a highly encouraging viable alternative to current leadership frameworks in the field of healthcare. This review articulates an integrated framework that connects neurocognitive mechanisms to leadership in hospitals. Forthcoming studies should more empirical evidence with better study design and more measurable outcomes in an organization.